Corporate Greening Through ISO 14001: A Rational Myth? - Boiral, Olivier (Organization science (Providence, R.I.), 2007)
The process used by organizations to integrate the ISO 14001 standard has not yet been the subject of extensive research in environmental management despite the rapid development of this standard, particularly in industrial companies. The results of a case study conducted among nine ISO 14001 certified Canadian organizations showed that adopting this standard tends to lead to a ceremonial behaviour intended to superficially show that the certified organizations conformed to the standard. Although rigorous compliance with the standard often resulted in real improvements, these improvements were primarily technical and administrative in nature. However, in most of the cases studied, daily practices remained somewhat decoupled from the prescriptions of the ISO 14001 system, of which employees generally had only a vague understanding. The organizations studied adopted different strategies to reconcile external pressures in favour of adopting this standard and internal constraints associated with a management system whose support varied from one case to the next. While the standard often appeared to be some sort of "rational myth" (Meyer and Rowan 1977) to which organizations superficially committed themselves, the adaptation to institutional pressures was not necessarily straightforward. Using the example of the ISO 4001 standard, our study helps to show how this myth can be integrated, transformed, and even created through rhetoric by organizations to resolve certain contradictions. This research also illustrates how adopting the ISO 14001 system can have an ambiguous effect on environmental management practices and performances.